Vertical and horizontal price transmission in the livestock and beef industry in Mexico - Rojas- Juárez, Lissete Abigail; Jaramillo- Villanueva, José Luis; Vargas-López, Samuel; Bustamante- González, Angel; Guerrero- Rodríguez, Juan de Dios (Ecosistemas y Recursos Agropecuarios, 2022)
This study aims to determine the behavior of the price transmission of steers and beef sales, along the supply chain and between spatially separated regions, in the states of Veracruz, Jalisco and Estado de Mexico. The data used were time series of monthly prices of steer and beef for the period 2003 to 2020. An Error Correction Model was estimated to determine the magnitude and speed of price response from one market to another. The results suggest asymmetry between the space markets of Mexico-Veracruz and Jalisco-Veracruz, with coefficients of -0.06 and -0.08, respectively, and significant (p ≤ 0.10), and show that producer prices in Veracruz react more quickly to a decrease in prices than when they are expanded. Incomplete and asymmetric price transmission is concluded and shown in vertical models. The main cause could be the high market concentration in national and regional meat processing.